Approximate answers to null queries with incomplete fuzzy information in object oriented database - Ban, Đoàn Văn; Tuấn, Trương Công; Thắng, Đoàn Văn (Journal of Computer Science and Cybernetics, 2012)
Reasoning analogy is an important inference tool in the study of artificial intelligence. Null queries are queries that find an answer to Null from the database system, often because of the imcompleteness of information in the database. Analogical reasoning are really useful to generate an approximate answers for Null queries. Analogical reasoning using fuzzy functional dependencies to answer null queries on fuzzy relational databases have been studied. In this paper, we present an approach to obtain an approximate answer for Null queries on Object-oriented database model with fuzzy information and uncertainty based on hedge algebra. Our approach was based on the concept semantic neighborhood of hedge algebra to build attribute fuzzy determination and method fuzzy determination